Primary Repair for Treating Acute Proximal Anterior Cruciate Ligament Tears: A Histological Analysis and Prospective Clinical Trial - Yang, Yue; Jin, Zhuangzhuang; Luo, Jianghua; Zhang, Delong; Shen, Peng; Zheng, Dianbin; Liu, Donghao; Bai, Lunhao (Frontiers in Bioengineering and Biotechnology, 2022)
Reconstruction surgery for acute proximal anterior cruciate ligament (ACL) tears remains controversial. Recently, ACL primary repair has received increasing attention in ACL treatment. This study aimed to explore the histological characteristics of ACL healing in primary repair and compare its therapeutic and prognostic results with the reconstruction of acute proximal ACL tears. Histological experiments using rabbits and a prospective clinical trial were conducted. We established a rabbit model of ACL primary repair, and histological changes were observed using haematoxylin and eosin (HE) and toluidine blue staining. We performed immunohistochemical analysis of CD34 and S-100 and measured the expression of collagen I and II using qRT-PCR, western blotting, and immunohistochemistry. The prospective clinical trial involved performing ACL primary repair and reconstruction in patients with acute proximal ACL tears to detect proprioception and evaluate the function of joints. We discovered that primary repair promoted cell proliferation in the tendon-bone transition and ligament portions, reduced osteoarthritis-like pathological changes, and maintained blood vessels and proprioceptors within the ACL. In the clinical trial, primary repair achieved similar therapeutic outcomes, including recovery of knee function and proprioception, in the follow-up period as ACL reconstruction. However, the primary repair had a significantly shorter operative time and lower cost than reconstruction. Therefore, doctors should consider the benefit of primary repair in treating acute proximal ACL tears.